Fatal non-occlusive mesenteric ischemia and the use of propranolol in paediatric burns. Issue 4 (June 2016) - Martinez, R.; Rogers, A.; Numanoglu, A.; Rode, H.
Highlights: Late onset abdominal complications in burns. Propranolol use in burnt children. Irreversible non occlusive mesenteric ischemia. Abstract: Abdominal complications without abdominal injury are infrequently seen in children with major burns. They are divided into those that occur early during the emergency phase of treatment and those that occur late in the course of treatment. One of the most serious late onset complications is non-occlusive mesenteric ischaemia associated with the use of vasoactive drugs. We report on 2 children who late in the course of their burn injury developed ischaemic necrosis of their entire intestine. Both were on propranolol, the administration of which was continued with even during the periods of septic shock which preceded their demise. We are of the opinion that endogenous catecholamine release during hypotensive and septic episodes in conjunction with β-adrenergic blockage from propranolol could lead to severe splanchnic vasoconstriction from unopposed α-adrenergic activity and hence critical circulation impairment to the bowel in the 2 children.